MOSQUE TOURISM PROGRAM MANAGEMENT TO FORM THE CHARACTER OF EARLY CHILDHOOD - Novan Ardy Wiyani; Aishath Shina; Rina Rizki Amalia (PEDAGOGIK : JURNAL PENDIDIKAN, 2026)
The educational function of mosques has not been optimally utilized to shape the character of early childhood due to the stigma that their presence in mosques only creates noise. The purpose of this study is to understand a management procedure for a mosque tourism program to develop the character of early childhood in kindergarten. The researcher used a case study research type. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman data analysis model. The results of the study indicate four management activities for mosque tourism programs to shape the character of children. First, planning activities, namely determining the objectives, program targets and methods, formulating SOPs, determining needs, determining the time and mosques to be visited. Second, organizing activities include coordination and socialization of the program. Third, implementation, where children explore various things in the mosque, pray dhuha and give alms. Fourth, supervision is carried out through monitoring and evaluation activities by the principal. The implication of this study is the formulation of a conceptual framework for managerial activities in mosque tourism programs to shape the character of early childhood children, namely formulating plans, organizing, implementing, and supervising mosque tourism programs in shaping the character of early childhood children.